2008
DOI: 10.1093/humrep/den207
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral responses of human Leydig cells to mumps virus infection or poly I:C stimulation

Abstract: BACKGROUNDThe immuno-privileged status of the testis is essential to the maintenance of its functions, and innate immunity is likely to play a key role in limiting harmful viral infections, as demonstrated in the rat. In men mumps virus infects Leydig cells and has deleterious effects on testosterone production and spermatogenesis. The aim of this study was to test whether mumps virus infection of isolated human Leydig cells was associated with an inhibition of their innate antiviral defences.METHODSLeydig cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 61 publications
(102 reference statements)
1
24
0
2
Order By: Relevance
“…The testicular innate antiviral responses have been previously demonstrated based on a series of pioneering studies on the expression and regulation of both interferons (IFNs) and antiviral proteins in the testis by Professor Jégou's group. [60][61][62]95,96 These investigators also showed that several defensins are expressed in murine and human testes, and may contribute to the innate antimicrobial defense. 97 Recent studies have revealed that various PRRs are abundantly expressed in testicular cells and initiate testicular innate immune responses.…”
Section: Testicular Innate Immunitymentioning
confidence: 94%
See 1 more Smart Citation
“…The testicular innate antiviral responses have been previously demonstrated based on a series of pioneering studies on the expression and regulation of both interferons (IFNs) and antiviral proteins in the testis by Professor Jégou's group. [60][61][62]95,96 These investigators also showed that several defensins are expressed in murine and human testes, and may contribute to the innate antimicrobial defense. 97 Recent studies have revealed that various PRRs are abundantly expressed in testicular cells and initiate testicular innate immune responses.…”
Section: Testicular Innate Immunitymentioning
confidence: 94%
“…60,61 Human Leydig cells show relatively weak antiviral activity compared with rat cells. 62 These observations raise an interesting question whether the human testis has a weaker innate defense system against viral infection compared with the murine testis. Notably, microbial infection frequently results in orchitis in humans.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…It has been suggested that this compartmentalization may be a consequence of differences between the male genital tract and peripheral tissues in both immunological and target cell properties [14], [15], [20], [21], [22], [23], [24], [25], [26], [27], [28]. Histopathologic studies of genital tissues from SIV-infected monkeys have confirmed that infection can occur at these sites [24], [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, no specific association was found between the expression of MxA or PKR mRNAs and the different antiviral activities of the type I IFNs against hMPV. Although the protein levels of MxA and PKR were not measured, and taking into consideration that in several studies researchers found a correlation between mRNA-levels and protein changes (8,11,13,15), these data suggest that these two proteins are not responsible for the differing antiviral activities displayed in these cells by the different type I IFNs.…”
Section: Resultsmentioning
confidence: 76%